Adsorption Efficiency of Carbon Prepared from Agricultural Waste Materials in Removing Basic Dye From Aqueous Solution - Tandon, Sucharita; Nandini, N. (Asian Journal of Chemistry, 2010)
Management of solid waste is the burgeoning issue of the current times. Agriculture waste is rich in organic material like cellulose, lignin etc. and can be of great use if utilized as right resource at right time and right place. In the current study agriculture waste material has been used for adsorption of colour from waste water. Sugarcane bagasse and paddy straw have been recycled to activated carbon and have been utilized and compared as the adsorbent for the removal of basic dye from aqueous solution. A basic dye, methylene blue has been used as the adsorbate. Two different mineral acids have been used for activation of raw material and it was observed that both H3PO4 and HNO3 were good activating agent but impregnation efficiency was in following order H3PO4 > HNO3. Adsorption experiments were conducted by varying several parameters namely pH, adsorbent dose, initial concentration of dye and contact time. It was observed that colour was effectively removed at all selected pH and the increase in activated carbon dose showed an increase in its adsorption efficiency. The percentage of colour removal decreased with an increase in the initial dye concentration. More than 90 % adsorption efficiency of dye from solution containing 10 mg/L of dye was attained with an adsorbent dosage of 0.1 g after 45 min of contact time at all pH. Results obtained indicate that agriculture waste material could be employed as a low cost alternative to commercial activated carbon in wastewater treatment for dye removal and can thus be a good example of wealth from waste.